2018
DOI: 10.3389/fmicb.2018.02806
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Methane Emissions From Acidified Dairy Slurry Is Related to Inhibition of Methanosarcina Species

Abstract: Liquid dairy manure treated with sulfuric acid was stored in duplicate pilot-scale storage tanks for 120 days with continuous monitoring of CH4 emissions and concurrent examination of changes in the structure of bacterial and methanogenic communities. Methane emissions were monitored at the site using laser-based Trace Gas Analyzer whereas quantitative real-time polymerase chain reaction and massively parallel sequencing were employed to study bacterial and methanogenic communities using 16S rRNA and methyl-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
2
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 55 publications
1
19
2
8
Order By: Relevance
“…The pattern of CH 4 production in the acidified tanks suggests that there was CH 4 production occurring, but at much lower rates than in the control tanks. In fact, Habtewold et al (2018) found that the methanogen abundance was reduced by 6% and the activity by 20% in the same acidified manure. They suggest that acidification inhibits, rather than kills, the methanogens present in manure (Habtewold et al, 2018).…”
Section: Resultsmentioning
confidence: 97%
“…The pattern of CH 4 production in the acidified tanks suggests that there was CH 4 production occurring, but at much lower rates than in the control tanks. In fact, Habtewold et al (2018) found that the methanogen abundance was reduced by 6% and the activity by 20% in the same acidified manure. They suggest that acidification inhibits, rather than kills, the methanogens present in manure (Habtewold et al, 2018).…”
Section: Resultsmentioning
confidence: 97%
“…However, it has been shown previously that e-SOX produces acidity even down to 4 cm 12 . Low pH values impede fermentation processes and methanogenesis, resulting in the reduction of methane emissions 21,22 . For example, a pH shift from pH 6.9 to 6.8 has been reported to decrease CH 4 production in flooded rice soil by 26% 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Real-time qPCR was performed using an Applied Biosystems StepOnePlus real-time PCR system using clear 96-well PCR plates (Bio-Rad Laboratories, Inc., Hercules, CA). The total and active fraction of the methanogen populations were quantified by targeting methyl coenzyme A reductase (mcrA) genes and transcripts, respectively, using mlas-mod F and mcrA-rev-mod R primers (Habtewold et al, 2018). The total and active fraction of the methanogen populations were quantified by targeting methyl coenzyme A reductase (mcrA) genes and transcripts, respectively, using mlas-mod F and mcrA-rev-modR primers (Habtewold et al, 2018).…”
Section: Nucleic Acid Extraction and Quantitative Real-time Pcrmentioning
confidence: 99%
“…Kavanagh et al (2019) reported 96% reductions of CH 4 and 85% of NH 3 with H 2 SO 4 acidification (to pH of 5.5). The mechanism of CH 4 reduction is still unclear, as H 2 SO 4 and pH reduction can disrupt microbial communities throughout all the processes of organic matter degradation as well as methanogens directly (Habtewold et al, 2018). Habtewold et al (2018) reported a methanogen reduction of 6% in abundance and 20% in activity between untreated and acidified dairy manure but observed no difference in the microbial communities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation